Effect of Chelator EDTA on Phyto-Remediation of Cadmium, Chromium and Lead and their Effect on Growth of Sunflower (Helianthus annuus L.): Effect of Metals on Growth of Sunflower (Biological Sciences - PJSIR, 2020)
The present study investigates the phyto-accumulation capacity of two cultivars of sunflower (Helianthus annuus L.) for heavy metals. Analysis of the data recorded ten weeks after sowing indicated that heavy metal application had significantly (p